2021
DOI: 10.1080/19336950.2021.1956226
|View full text |Cite
|
Sign up to set email alerts
|

Database mining analysis revealed the role of the putative H+/sugar transporter solute carrier family 45 in skin cutaneous melanoma

Abstract: Metabolic reprogramming is common in various cancers. Targeting metabolism to treat tumors is a hot research topic at present. Among them, changes in glucose metabolism in cancer have been widely studied. The Warburg effect maintains a high metabolic level in the tumor, accompanied by changes in glucose transporters. The transmembrane transport of sugar was previously thought to be mediated by SGLT and GLUT. Recently, the Solute Carrier Family(SLC) 45 family may be the third sugar transporter. But the role and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 25 publications
0
16
0
Order By: Relevance
“…Conventional treatment of gastric cancer thus far has generally been unsatisfactory [ 12 ]. Immunotherapy has achieved positive initial results in the clinical treatment of gastric cancer and has a positive outlook as a treatment method [ 13 ]. Neoantigen production, genomic instability, and viral or bacterial infection may be favorable factors for immunotherapy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Conventional treatment of gastric cancer thus far has generally been unsatisfactory [ 12 ]. Immunotherapy has achieved positive initial results in the clinical treatment of gastric cancer and has a positive outlook as a treatment method [ 13 ]. Neoantigen production, genomic instability, and viral or bacterial infection may be favorable factors for immunotherapy [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study found that SALL4 induced mitochondrial oxidative phosphorylation (OXPHOS) during tumorigenesis [118] (Figure 7). A phenomenon commonly called the Warburg effect usually occurs in during tumorigenesis [119]. Cancer cells usually rewire their bioenergetic metabolism by changing from mitochondrial OXPHOS to aerobic glycolysis, despite the presence of oxygen.…”
Section: Sall4 Induces Mitochondrial Oxidative Phosphorylation During...mentioning
confidence: 99%
“…UVM originates in the uveal tract and includes the iris, ciliary body, and retinal choroid ( 2 ). It is worth mentioning that UVM and cutaneous malignant melanoma (the most common type of melanoma) have significant differences in risk factors, pathological features, and treatment outcomes ( 3 , 4 ). However, the current treatment options for UVM are still limited, especially for the treatment of advanced UVM, which is still largely based on the treatment options for cutaneous malignant melanoma ( 5 ).…”
Section: Introductionmentioning
confidence: 99%